Pemanfaatan IoT untuk Monitoring Kualitas Air dan Pelatihan Pembuatan Abon Ikan di Pokdakan Mina Jaya Banyumas - Yuliantoro, Prasetyo; Latifasari, Nurul; Setyawan, Agung Cahyo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Mina Jaya fish farming group in Banyumas Regency faces significant challenges in freshwater fish farming, primarily due to poor water quality caused by household waste contamination. This issue leads to high fish mortality rates, especially for mujaer, catfish, and tilapia, significantly reducing harvest yields and economic returns. To address these problems, this community service program introduced Internet of Things (IoT) technology for real-time water quality monitoring. The program also included training on IoT usage and post-harvest management, specifically the production of fish floss (abon), to enhance the value of fish products. IoT implementation proved effective in reducing fish mortality, improving water conditions, and increasing operational efficiency. Furthermore, the post-harvest training enabled the group to diversify their products and increase income. These results demonstrate the potential of combining modern technology and community empowerment to overcome aquaculture challenges and improve productivity. The program recommends expanding IoT usage, continuing post-harvest product diversification, and fostering sustainable collaboration to maximize long-term benefits.